The (II)liberal shift in Polish migration discourse: a multimodal analysis of civic platform’s portrayal of immigrants - Marcin Kosman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Since the outbreak of the 2015 European migration crisis, Polish discourse on migration has undergone significant changes. While in the past the discursive construal of the immigrant was relatively neutral, since 2015 it has been subject to vilification of the Muslim Other. So far, research on Polish migration discourse has concentrated on right-wing and conservative discourses, while the liberal one has been understudied. Combining the Discourse-Historical Approach with selected methods of multimodal analysis, the study offers a thorough investigation of the discourse of the liberal Civic Platform, Poland’s ruling party since the end of December 2023. The triangulation of methods thus allowed to verify how the visual and verbal work together to form a coherent whole. In addition, the findings were interpreted through the lens of social theories of securitization and orientalization, which allowed to go beyond the discursive dimension. The application of the discussed theories helped to place the findings in the broader context socio-political context of Europe, discussing the intricate dynamics of power, identity, and the construction of “the other.” The results suggest that, despite its liberal profile, Civic Platform demonized migration and immigrants, portraying them as a threat to Polish security. In addition, the then government was presented as facilitating human trafficking and collaborating with criminals. Overall, the analyzed discourse is strikingly similar to contemporary far-right discourses on migration, which is surprising in light of previous research on liberal discourse, which has tended to emphasize the humanitarian dimension of migration and the need for solidarity with migrants.